(untitled) (Ciudades, 2018)
The built of state-subsidized apartments lived, in France, “a golden age” between 1946 and 1975. In the eighties the “aid to the brick” shifted to the “aid to the people”, and in the nineties the production of houses gets stabilized around 310.000 apartments per year. Nevertheless, with the new century, the political objective of “social mixture” is completely assumed by institutions. The article denounces the contradiction between this objective and the politics of property access, promoted by all the French governments for nearly a century, this contradiction is neatly manifested in the formation of Ghettos in the state-subsidized housing areas.